A QUANTITATIVE DESCRIPTIVE ANALYSIS OF STUDENTS' PERCEPTIONS OF TEACHING STRATEGY EFFECTIVENESS AND TEACHER INTERACTION PATTERNS AT SMAN 1 KUTA BARO - Anzora, Anzora; Aryani, Irma; Renggayoni, Deya Reta; Mutmainnah, Hafizhatul; Selina, Selina (Numeracy, 2026)
This research is motivated by the significance of student perception as an evaluation indicator for the quality of mathematics instruction at the secondary school level. The objective of this study is to analyze students' perceptions regarding the effectiveness of teaching strategies and teacher interaction patterns at the Senior High School level 1 Kuta Baro. This study employs a quantitative descriptive approach, involving a sample of 26 students from the tenth and eleventh grades, selected through a purposive sampling technique. Data were collected using a closed-ended questionnaire instrument consisting of 44 items on a five-point Likert scale. The results indicate that students' perceptions of teaching strategies and teacher interaction patterns fall into the 'good' category, with an overall mean score of 3.93. The dimensions of classroom interaction and motivational support received the highest ratings; however, findings suggest that learning grouping strategies and teacher dominance in classroom communication still require improvement. This study concludes that although the learning process is considered effective, innovation in group management and a shift in teaching patterns toward student-centered learning are necessary to optimize active participation in the classroom.